Aquatic physiotherapy: a vestibular rehabilitation option - Pereira,Carolina Maria Maia (2021)
Abstract Introduction: Vestibular rehabilitation is a fundamental resource for vestibular symptom control. Its performance in the aquatic environment is considered safe for the physical activities of the elderly, because they act simultaneously on musculoskeletal disorders and balance improvement. Objective: To evaluate the effects of an aquatic physiotherapy protocol in individuals with peripheral vestibular alterations. Methods: This was an interventional case study with a paired intentional sample of four subjects, who were selected for convenience. The subjects, all of them diagnosed with peripheral vestibulopathy, were submitted to twelve sessions of aquatic physiotherapy for vestibular rehabilitation, being evaluated for dizziness in three moments: initial, after six sessions and at the end of the sessions. The tests applied were: unipodal support to measure static balance, the Fukuda stepping test, which estimates the dynamic balance and the dizziness handicap inventory protocol, aimed at verifying how dizziness influences daily life. Results: When analyzing the static balance, initially the individuals were in the adaptive and abnormal dimensions, and all reached normality at the end of the protocol. Regarding the dynamic balance, the individuals initially showed marked impairment in the angular deviation, mainly to the side of pathology (75% to the left and 25% to the right), achieving improvement at the end of the study. However, it failed to reach statistical significance. The dizziness handicap inventory showed a statistically significant difference in its totality (p = 0.0414), which addresses the physical, functional and emotional factors. Conclusion: In conclusion, the aquatic physiotherapy protocol for vestibular rehabilitation of patients with peripheral impairment was positively assessed by the participants, considering the improvement in dizziness (static and dynamic) and its impact on daily activities.